Inkjet-based oligonucleotide synthesis reagents: Formulation optimization and comparison of acetonitrile and propylene carbonate applications - Yu Xiao; Yongjin Peng; Zhen Rong; Xiaoyang He; Fei Sun; Shengqi Wang (Results in Chemistry)
With the rapid development of synthetic biology and genomic research, the demand for high-throughput DNA synthesis has been steadily increasing. Inkjet printing technology has gradually emerged as an ideal method for customized oligonucleotide synthesis due to its high precision and flexibility. However, the traditional solvent acetonitrile (ACN), due to its low viscosity and high permeability, fails to meet the stability requirements for inkjet head operation, resulting in unstable droplet formation that affects synthesis accuracy and efficiency. This study proposes propylene carbonate (PC) as a novel solvent for inkjet DNA synthesis, comparing the stability of inkjet droplets and the performance of oligonucleotide synthesis between PC and ACN, while further optimizing the concentrations of phosphoramidite monomers and activator. Experimental results indicate that the PC solvent not only exhibits good inkjet stability but also significantly enhances the purity of oligonucleotide synthesis products and stepwise coupling efficiency under optimal conditions. When synthesizing a target sequence of 30 nucleotides, a stepwise coupling efficiency of 99.01 % was achieved. This study achieved a new DNA synthesis reagent formulation that supports inkjet-based DNA synthesis and exhibits excellent coupling efficiency. This research outcome is expected to promote the further development of high-throughput DNA synthesis using inkjet technology.